2008
DOI: 10.1017/s0265021507002724
|View full text |Cite
|
Sign up to set email alerts
|

Association between GSTP1 gene polymorphism and serum α-GST concentrations undergoing sevoflurane anaesthesia

Abstract: Although alpha-glutathione-S-transferase levels were elevated in all patients after sevoflurane anaesthesia, levels remained high at 24 h in patients with glutathione-S-transferase P1 Ile105Val genotypes compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…A possible association was observed between the Val105Val genotype and increased susceptibility to these diseases in alcoholics (7.3% in healthy Brazilian vs 28.6% in pancreatitis cases) (Burim et al, 2004). Kaymak et al (2008) found that heterozygous (GSTP1 I105V) individuals in a Turkish population undergoing sevoflurane anesthesia showed an increased level of serum α-GST enzyme within 24 h after anesthesia. International studies have indicated that the Val105 allele is more common in African-Americans (42%), but less common among Chinese (22%), Taiwanese (18%), and Japanese (14%) populations compared to European-Americans (33%), while allele Val114 is less often observed in African-Americans (5%) than in European-Americans (9%) (Watson et al, 1998;Zhong et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…A possible association was observed between the Val105Val genotype and increased susceptibility to these diseases in alcoholics (7.3% in healthy Brazilian vs 28.6% in pancreatitis cases) (Burim et al, 2004). Kaymak et al (2008) found that heterozygous (GSTP1 I105V) individuals in a Turkish population undergoing sevoflurane anesthesia showed an increased level of serum α-GST enzyme within 24 h after anesthesia. International studies have indicated that the Val105 allele is more common in African-Americans (42%), but less common among Chinese (22%), Taiwanese (18%), and Japanese (14%) populations compared to European-Americans (33%), while allele Val114 is less often observed in African-Americans (5%) than in European-Americans (9%) (Watson et al, 1998;Zhong et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Advancements in pharmacogenomics have demonstrated that some of these differences can be explained by genetic factors [1], especially by polymorphisms in genes involved in the pharmacokinetics and pharmacodynamics of the anaesthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphisms were studied extensively for various substances and diseases including the metabolism of acetaminophen, Parkinson disease, and cancer. Pioneering investigations on association of the hGSTP1 genetic variability and the toxicity indicator in anesthesia were performed by Kaymak et al [39]. The results demonstrated a correlation between the Ile105Val polymorphism in hGSTP1 gene and mild hepatotoxicity in patients undergoing general anesthesia with sevoflurane.…”
Section: Genetic Variability Of Gst Enzymesmentioning
confidence: 99%
“…However, there are few studies that would additionally include the genetic variability in these analyses. Kaymak et al [39] attempted to find a correlation between the hGSTP1 polymorphism and the level of the α-GST enzyme in the serum of patients anesthetized with sevoflurane. The Ile105Val variant of the hGSTP1 gene is responsible for maintaining a high level of the enzyme in the serum after 24 hours from anesthesia, yet the choice of gene subjected to analysis is quite astonishing.…”
Section: Potential Of Gst Genetics In Prognosing Safe Anesthesiamentioning
confidence: 99%